Trypanosoma cruzi and Toxoplasma gondii Induce a Differential MicroRNA Profile in Human Placental Explants - Medina, Lisvaneth; Castillo, Christian; Liempi, Ana; Guerrero-Muñoz, Jesús; Rojas-Pirela, Maura; Maya, Juan Diego; Prieto, Humberto; Kemmerling, Ulrike (Frontiers in Immunology, 2020)
Trypanosoma cruzi and Toxoplasma gondii are two parasites than can be transmitted from mother to child through the placenta. However, congenital transmission rates are low for T. cruzi and high for T. gondii. Infection success or failure depends on complex parasite-host interactions in which parasites can alter host gene expression by modulating non-coding RNAs such as miRNAs. As of yet, there are no reports on altered miRNA expression in placental tissue in response to either parasite. Therefore, we infected human placental explants ex vivo by cultivation with either T. cruzi or T. gondii for 2 h. We then analyzed the miRNA expression profiles of both types of infected tissue by miRNA sequencing and quantitative PCR, sequence-based miRNA target prediction, pathway functional enrichment, and upstream regulator analysis of differentially expressed genes targeted by differentially expressed miRNAs. Both parasites induced specific miRNA profiles. GO analysis revealed that the in silico predicted targets of the differentially expressed miRNAs regulated different cellular processes involved in development and immunity, and most of the identified KEGG pathways were related to chronic diseases and infection. Considering that the differentially expressed miRNAs identified here modulated crucial host cellular targets that participate in determining the success of infection, these miRNAs might explain the differing congenital transmission rates between the two parasites. Molecules of the different pathways that are regulated by miRNAs and modulated during infection, as well as the miRNAs themselves, may be potential targets for the therapeutic control of either congenital Chagas disease or toxoplasmosis.